Sekolah dan Madrasah sebagai Organisasi Pendidikan: Sistem Sosial, Dinamika Sosial dan Budaya Organisasi - Hasan, Muflikhul; Idi, Abdullah; Karoma, Karoma; Mahyudin, Edy (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze schools and madrasahs as educational organizations from the perspectives of social systems, social dynamics, and organizational culture. This research is a literature review or library study. The data sources consist of books, scientific journals, research reports, and official documents related to schools and madrasahs as educational organizations. Data collection was carried out through document analysis, while the data were analyzed using content analysis techniques in a systematic and critical manner. Based on the results and discussion, it can be concluded that schools and madrasahs play a strategic role as social organizations that not only perform educational functions but also serve as platforms for the socialization of societal values, norms, and culture. A well-structured social system, harmonious relationships, and effective communication within the educational environment significantly contribute to shaping students’ character and social identity. As agents of cultural transmission and social solidarity, schools and madrasahs strengthen community integration through the internalization of universal and religious values. In facing modernization and technological advancement, these educational institutions are required to be adaptive by fostering a positive, inclusive, and innovative organizational culture. The exemplary behavior of teachers becomes a key factor in instilling moral values, shaping character, and creating a conducive and competitive learning environment.